Impact of health education intervention in promoting cervical cancer screening among rural women of Chengalpattu district - The community based interventional study - I. Thahirabanuibrahim; Muthunarayanan Logaraj (Elsevier, 2021)
Background: The incidence and prevalence of cervical cancer is on rise among rural women in Tamil Nadu. The scientific community is lobbying strongly in providing health education as a pre-emptive measure in reducing morbidity and mortality due to cervical cancer. This research explores the effective way of health communication towards the promotion of cervical cancer prevention and screening. Materials and methods: The community based interventional study was carried out from, sample of 370 rural women from Chengalpattu district of tamilnadu selected using multistage sampling method.A baseline and end-line data were collected using standard questionnaire "Cervical Cancer Awareness Measure tool kit 2.1".After baseline data collection, health education on cervical cancer was imparted using Audio-Visual sources depicting the signs and symptoms, preventive measures, and the significance of getting screened at regular intervals for cervical cancer were exhibited in the local language. Call for screening camp was announced at regular intervals.Descriptive statistics, Paired t-test and Mean difference with 95% CI and screening rate from the women attending the screening camp was calculated. Results: Women aged 40-49 with 44.5% was the major study participants The significant difference was found to the factors, warning sign(p-value = 0.03; MD = 7.59; CI = 3.27-3.29), Risk factors(p-value = 0.02; MD = 21.32; CI = 21.2-21.4) and attitude towards screening (p-value = 0.003; MD = 0.85; CI = 0.79-0.81).The percentage of Screening rate was 31.1% after health education. Conclusion: Thus, the above-mentioned health education model has proved to be efficacious on cervical cancer prevention Research can be further up-scaled by integrating the benefit incidence and comparing with other health education models.